Optimising online marketing resources: SEO strategy. (1st January 2012) - Pandey, Anuja
The dynamics of conducting business is changing. Across the world, internet is becoming the major source to promote the business and its products. With increased penetration of internet in India, web traffic has increased exponentially. The role of search engines has become very important as search engines are a major tool to dig information on web. The purpose of this paper is to identify and measure the performance of keywords and evaluate the performance of search engine and suggest online marketing strategy. The paper presents the results of web traffic at organisation portal delivered by search engine. The period of study is one and half years. The study focuses on the most frequently used keywords and the search engine most effective in diverting web traffic. The paper provides insight into the techniques that are successful in search engine optimisation and used to ensure high traffic generation. Also, some of the keywords are more often used than others.